Manajemen Risiko Pada Aktivitas Distribusi Pangan KJP Di Kepulauan Seribu Menggunakan Metode House Of Risk - Roberta H. A. Tanisri; Oki Widhi Nugroho; Sonny Nugroho Aji (Program Studi Teknik Industri, Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2022)
PD PSJ is a company engaged in the distribution of foodstuffs and basic needs, especially the people PD PSJ is a company engaged in the distribution of foodstuffs and basic needs, especially the people of Jakarta. Along with the government's program related to the procurement of KJP cheap foodstuffs, the KJP food distribution process is in collaboration with PD PSJ. KJP food distribution activities are carried out throughout the DKI Jakarta area, including the Thousand Islands. In the process, there were several obstacles experienced by the officers. To reduce the risk of a late KJP food distribution supply, management carried out several policies related to risk management. The House of Risk (HOR) method is one of the methods to identify several activities and risks that can occur in the supply chain process of goods. This research applies the HOR method to obtain recommendations for improvements in the process of distributing KJP goods. The results of data processing and analysis using the HOR method obtained the greatest recommendation for improvement is to conduct training to field officers and improve communication both internally and externally.